A high temperature resistant waterborne coating composition and a method of making the same

CN122790488APending Publication Date: 2026-09-22ZHAOQING ZHONGQIAO ELECTRIC IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610969074.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0004]本发明所要解决的技术问题是提供一种耐高温水性涂料组合物及其制备方法,旨在解决水性涂料组合物在保持低VOC的同时,因树脂极性基团以及水分的残留导致涂料涂层耐高温性能下降的问题

Benefits of technology

[0007]由上述技术方案可知,本公开示例性实施例中至少具备以下优点和积极效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122790488A_ABST
    Figure CN122790488A_ABST
Patent Text Reader

Abstract

The application belongs to the field of paint, and provides a high-temperature-resistant water-based paint composition and a preparation method thereof, the preparation method comprising the following steps: adding a polyester polymer into deionized water and stirring uniformly to obtain a premixture, then adding a polyhydric alcohol additive and an ester exchange additive, and heating and stirring to react, to obtain an activated polyester dispersion liquid; adding an acrylic polymer and a phenyl boronic acid crosslinking agent into the activated polyester dispersion liquid, adjusting the pH to alkaline, heating and stirring to react, to obtain a modified solution; adding an organic silicon polymer and a metal salt into the modified solution, and stirring and dispersing, to obtain the high-temperature-resistant water-based paint composition. The water-based paint composition prepared by the above method still retains good high-temperature resistance while maintaining low VOC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of coating technology, specifically to a high-temperature resistant water-based coating composition and its preparation method. Background Technology

[0002] As a crucial shielding and mechanical protection structure for cables, the cable braid layer is constantly subjected to the effects of current heating, ambient temperature rise, and thermal stress generated by equipment operation. Therefore, it typically requires a protective coating to improve its corrosion resistance, insulation, and high-temperature resistance. Existing protective coatings for cable braid layers mainly include solvent-based and water-based coatings. Solvent-based coatings, using organic solvents as the dispersion medium, offer advantages such as good film-forming properties, fast curing speed, and dense coatings. However, they release large amounts of volatile organic compounds (VOCs) during preparation and application, making it difficult to meet increasingly stringent environmental protection requirements. In contrast, low-VOC water-based coatings, using water as the primary dispersion medium, achieve water solubility or dispersibility of the resin by introducing hydrophilic groups such as carboxyl and hydroxyl groups, significantly reducing VOC emissions. Therefore, they are gradually becoming an important development direction in the field of cable braid layer protection.

[0003] However, low-VOC waterborne coatings still suffer from insufficient high-temperature resistance in applications such as cable braids that require long-term exposure to high temperatures. On the one hand, due to the high latent heat of vaporization of water, waterborne coatings experience slow water removal during curing, leading to residual moisture. This affects the crosslinking reaction and density of the resin system, resulting in a less dense coating structure that is more prone to thermal deformation, creep, and performance degradation during high-temperature service. On the other hand, the hydrophilic groups in the resin molecular chain have strong polarity and hygroscopicity, easily adsorbing moisture from the environment. Under high-temperature conditions, the adsorbed moisture vaporizes, generating internal stress. Simultaneously, the increased thermal motion of polar groups plasticizes the resin network, causing a decrease in the coating softening temperature and a reduction in mechanical properties. This limits the further application of low-VOC waterborne coatings in the field of high-temperature protection for cable braids. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a high-temperature resistant water-based coating composition and its preparation method, aiming to solve the problem that the high-temperature resistance of the coating is reduced due to the residual polar groups of resin and moisture while maintaining low VOC in the water-based coating composition.

[0005] To address the aforementioned technical problems, a method for preparing a high-temperature resistant water-based coating composition is proposed, the method comprising the following steps: S1. Add polyester polymer to deionized water and stir until homogeneous to obtain a premix. Then add polyol auxiliaries and transesterification auxiliaries, heat and stir to react, and obtain activated polyester dispersion. S2. Add propylene polymer and phenylboronic acid crosslinking agent to the activated polyester dispersion, adjust the pH to alkaline, heat and stir to react, and obtain a modified solution, wherein the propylene polymer contains hydroxyl groups; S3. Add organosilicon polymer and metal salt to the modified solution, stir and disperse to obtain a high-temperature resistant water-based coating composition, wherein the organosilicon polymer contains hydroxyl groups and the metal ions in the metal salt are hard acid ions.

[0006] In addition, a high-temperature resistant waterborne coating composition is proposed, which is prepared by the above-described method for preparing a high-temperature resistant waterborne coating composition.

[0007] As can be seen from the above technical solutions, the exemplary embodiments disclosed herein possess at least the following advantages and positive effects: On the one hand, due to the use of deionized water as the dispersion medium and the construction of a waterborne resin system by polyester polymer, propylene polymer, organosilicon polymer and phenylboronic acid crosslinking agent, the main film-forming components in the system exist in polymer form. During preparation and use, there is no need to add a large amount of organic solvent as a dissolving and diluting medium. Moreover, polyol additives, phenylboronic acid crosslinking agents and organosilicon polymers preferentially participate in the construction of the resin network rather than volatilize and escape, thereby achieving the effect of low VOC emissions.

[0008] On the other hand, through the technical means of synergistically constructing a multi-level crosslinking network using polyol auxiliaries, ester exchange aids, propylene polymers, phenylboronic acid crosslinking agents, organosilicon polymers, and metal salts, the polyol auxiliaries undergo ester exchange reactions with polyester polymer segments under the action of ester exchange aids, causing the polyester segments to redistribute and introduce more reactive hydroxyl sites, providing a foundation for subsequent crosslinking reactions. The propylene polymer, as a reactive segment containing hydroxyl groups, along with the polyester polymer and organosilicon polymer, serves as a reaction participant in the phenylboronic acid crosslinking agent. Its hydroxyl groups can undergo borate esterification reactions with the phenylboronic acid crosslinking agent, allowing different polymer segments to form a multi-point connection structure through the same borate ester crosslinking center, thereby improving the uniformity and network continuity of the system's crosslinking. Subsequently, the phenylboronic acid crosslinking agent, as a crosslinking center, gradually forms a reversible three-dimensional borate ester network structure with the hydroxyl groups of each component in the system, enabling... The system transforms from a linear or branched structure into a dense cross-linked network. Simultaneously, the organosilicon polymer participates in network construction through terminal hydroxyl groups, introducing Si-O-Si heat-resistant segments. During film formation and curing, these segments migrate and accumulate on the surface, forming a low-surface-energy hydrophobic layer. This hydrophobic layer reduces the interfacial energy and wettability of the coating surface, allowing moisture within the system to migrate more easily to the surface under the influence of concentration gradients and interfacial energy, and then desorb and escape at the interface, thus promoting the removal of residual moisture and reducing retention. Furthermore, the metal salt coordinates with oxygen atoms in the carbonyl oxygen, silicon oxygen structures, and borate ester network within the system. The metal ions are hard acid ions, and according to the hard-soft acid-base theory, they have selective affinity for the oxygen donors, which are hard base ions, forming multi-point coordination bridging structures and stabilizing the dynamic bonds of the borate ester, thereby improving the structural integrity and stability of the cross-linked network. Through these effects, the problems of high resin polar group content and residual moisture retention leading to decreased high-temperature resistance in existing technologies are further overcome, thus achieving an improved high-temperature resistance of the coating. Attached Figure Description

[0009] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this disclosure and, together with the description, serve to explain the principles of this disclosure. It is obvious that the drawings described below are merely some embodiments of this disclosure, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort. In the drawings: Figure 1 This is a schematic diagram of a method for preparing a high-temperature resistant water-based coating composition in one embodiment; Figure 2 This is a schematic diagram of step S1 in the preparation method of the high-temperature resistant water-based coating composition in one embodiment; Figure 3 This is a schematic diagram of step S2 in the preparation method of the high-temperature resistant water-based coating composition in one embodiment; Figure 4This is a schematic diagram of step S3 in the preparation method of the high-temperature resistant water-based coating composition in one embodiment. Detailed Implementation

[0010] Exemplary embodiments will now be described more fully with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in many forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this disclosure will be more thorough and complete, and will fully convey the concept of the exemplary embodiments to those skilled in the art.

[0011] Furthermore, the described features or characteristics may be combined in any suitable manner in one or more embodiments. Numerous specific details are provided in the following description to give a thorough understanding of embodiments of this disclosure. However, those skilled in the art will recognize that the technical solutions of this disclosure may be practiced without one or more of the specific details, or other method steps may be employed. In other instances, well-known methods, implementations, or operations are not shown or described in detail to avoid obscuring various aspects of this disclosure.

[0012] The flowcharts shown in the accompanying drawings are merely illustrative and do not necessarily include all content and operations / steps, nor do they necessarily have to be performed in the described order. For example, some operations / steps can be broken down, while others can be combined or partially combined; therefore, the actual execution order may change depending on the specific circumstances.

[0013] Please refer to Figure 1 This invention proposes a method for preparing a high-temperature resistant water-based coating composition, the preparation method comprising the following steps: S1. Add the polyester polymer to deionized water and stir until homogeneous to obtain a premix. Then add the polyol auxiliaries and transesterification auxiliaries, heat and stir to react, and obtain an activated polyester dispersion.

[0014] In step S1, the polyester polymer includes at least one of polyethylene terephthalate, polybutylene terephthalate, polypropylene terephthalate, polybutylene adipate, and polyethylene adipate; the polyol auxiliaries include at least one of ethylene glycol, propylene glycol, diethylene glycol, neopentyl glycol, trimethylolpropane, pentaerythritol, and polyethylene glycol; and the transesterification auxiliaries include at least one of tetrabutyl titanate, tetraisopropyl titanate, titanium acetylacetonate, stannous octoate, and dibutyltin dilaurate.

[0015] By dispersing polyester polymers in an aqueous phase and activating the surface segments of polyester particles with the aid of polyol auxiliaries and transesterification auxiliaries, more active groups capable of participating in subsequent crosslinking reactions are formed at the ends and near-surface regions of the polyester molecular chains. This process promotes chain reorganization and structural optimization, improving the bonding ability and crosslinking efficiency between the polyester resin and the crosslinking components. The resulting crosslinked network is denser and more stable, effectively reducing the plasticizing effect and high-temperature migration effect of polar groups and residual moisture on the coating. While maintaining the low VOC characteristics of the aqueous system, it improves the coating's heat resistance stability, mechanical property retention, and structural integrity under high-temperature conditions, thereby enhancing the coating's high-temperature performance.

[0016] Step S1 includes: S1.1 Add the polyester polymer to deionized water and stir at 300-600 rpm for 20-40 min. Then raise the temperature to 40-60℃ and continue stirring for 10-30 min to obtain a premix. The mass ratio of polyester polymer to deionized water is (15-20):(60-70).

[0017] By controlling the ratio of polyester polymer to deionized water and continuously stirring at 300-600 rpm, the polyester particles are fully wetted and uniformly dispersed in the aqueous phase, reducing particle agglomeration. Subsequently, the temperature is raised to 40-60℃ and stirring is continued, which helps to improve the mobility of polyester chain segments, promotes the penetration and contact of water phase with the surface of polyester particles, and forms a stable and uniform pre-dispersion state in the system. This provides good mass transfer conditions for the activation reaction of polyester surface chain segments, and at the same time helps to improve the uniformity and controllability of the subsequent activation process, thereby ensuring the stable preparation of activated polyester dispersion.

[0018] S1.2 Add polyol additive to the premixture. The amount of polyol additive added is 3~20wt% of the polyester polymer mass. Control the stirring speed to 400~800rpm and stir the reaction at 60~80℃ for 30~90min to obtain a predispersant.

[0019] By adding an appropriate amount of polyol auxiliaries to the premix and continuously stirring the reaction at 60-80℃, the polyols can be fully diffused to the surface and near-surface region of the polyester particles, enhancing the wetting and plasticizing effect on the polyester segments, improving the segment mobility and surface activity, thereby promoting further uniform dispersion of the polyester particles and the formation of a stable dispersion system. Simultaneously, the polyols can provide reaction sites for subsequent polyester segment activation and crosslinking reactions, improving the interaction efficiency between subsequent components and the polyester.

[0020] S1.3 Add transesterification aid to the pre-dispersion liquid. The amount of transesterification aid added is 0.1~5wt% of the polyester polymer mass. Control the stirring speed at 300~700rpm and react at 60~80℃ for 40~60min to obtain activated polyester dispersion.

[0021] By adding an appropriate amount of transesterification aid to the pre-dispersion solution and maintaining the reaction at 60-80℃, a controlled transesterification reaction can be promoted on the surface of the polyester molecular chain. This reorganizes the chain segment structure on the surface of the polyester particles, increases the exposure of terminal hydroxyl active sites, and enhances the reactivity of the polyester particle surface. Simultaneously, the transesterification process mainly occurs in the particle surface region, improving the bonding ability between subsequent crosslinking components and the polyester while avoiding excessive degradation of the main polyester structure.

[0022] S2. Add propylene polymer and phenylboronic acid crosslinking agent to the activated polyester dispersion, adjust the pH to alkaline, heat and stir to react, and obtain a modified solution, wherein the propylene polymer contains hydroxyl groups.

[0023] In step S2, the propylene polymer includes at least one of hydroxyethyl methacrylate, hydroxyethyl acrylate, and hydroxypropyl methacrylate, and the phenylboronic acid crosslinking agent includes at least one of phenylboronic acid, 1,4-phenyldiboronic acid, and 4,4'-biphenyldiboronic acid.

[0024] By introducing hydroxyl-containing propylene polymers and phenylboronic acid crosslinking agents into an activated polyester dispersion and reacting them under alkaline conditions, phenylboronic acid groups can undergo borate esterification reactions with polyester segments, polyols, and hydroxyl groups in the propylene polymer. This establishes a multi-point connection structure between different polymer segments, forming a uniform and continuous three-dimensional crosslinked network. This crosslinked network effectively restricts segment movement, reduces the degree of freedom of polar hydroxyl groups in the system and their adsorption capacity for moisture, while reducing free volume and moisture retention space. It also inhibits the migration and aggregation of moisture and low-molecular-weight components under high-temperature conditions, thereby improving the structural stability, heat resistance, and performance retention of the coating under high-temperature environments.

[0025] Step S2 includes: S2.1 Add the propylene polymer to the activated polyester dispersion, control the temperature at 40~60℃, stir at 400~800rpm, and continue stirring for 20~60min to obtain a mixture, wherein the mass ratio of propylene polymer to deionized water is (20~25):(60~70).

[0026] Adding the propylene polymer to the activated polyester dispersion at 40–60°C and stirring at 400–800 rpm for 20–60 min promotes uniform dispersion of the propylene polymer particles in the system and ensures sufficient contact with the activated polyester polymer. This allows the polymer chains to effectively entangle and become compatible through intermolecular forces, preventing agglomeration or phase separation caused by excessively high local concentrations. Simultaneously, the suitable temperature enhances the mobility of the polymer chains, promoting interfacial fusion and the formation of a stable dispersion structure, while continuous stirring increases the contact area between the two phases, improving system homogeneity. Preparing the propylene polymer and deionized water at a specific mass ratio not only ensures good flowability and dispersion stability but also allows the propylene polymer to be uniformly embedded in the polyester dispersion system, providing more active contact sites for subsequent crosslinking reactions.

[0027] S2.2 Add a phenylboronic acid crosslinking agent to the mixture, adjust the pH of the system to 8.5-9.5 using an alkaline additive, heat to 60-70℃, and stir at 400-600 rpm for 1-2 hours to obtain a modified solution. The amount of phenylboronic acid crosslinking agent added is 5-15 wt% of the polyester polymer mass, and the alkaline additive includes at least one of ammonia, triethylamine, dimethylethanolamine, or sodium hydroxide solution.

[0028] Adding a phenylboronic acid-based crosslinking agent to the mixture and adjusting the pH to 8.5–9.5 using an alkaline auxiliaries before reacting at 60–70°C is beneficial for activating the reactivity of the phenylboronic acid groups, enabling them to undergo dynamic borate esterification reactions with oxygen-containing functional groups such as hydroxyl groups in polyester and propylene polymers, forming a stable and adjustable crosslinked network structure. An alkaline environment promotes the conversion of boric acid to borate, improving crosslinking efficiency and reaction rate, while suitable temperature and stirring conditions help ensure uniform dispersion and sufficient contact of the phenylboronic acid-based crosslinking agent in the system, avoiding uneven local crosslinking or gelation. By controlling the amount of phenylboronic acid crosslinking agent added, the crosslinking density can be effectively increased while ensuring the stability of the system. This allows the polyester and propylene segments to form a synergistically reinforced three-dimensional network structure, which not only improves the structural integrity and dispersion stability of the modified solution but also enhances the mechanical strength, water resistance, solvent resistance, and heat resistance of the subsequent film. At the same time, the dynamic borate ester bonds endow the system with certain stress relief and structural adjustment capabilities, which helps to reduce the risk of cracking or performance degradation of the coating due to internal stress accumulation under high temperature or long-term service conditions.

[0029] In one embodiment, step S2 includes: S2.1 Add the propylene polymer to the activated polyester dispersion, control the temperature at 40~60℃, stir at 400~800rpm, and continue stirring for 20~60min to obtain a mixture, wherein the mass ratio of propylene polymer to deionized water is (20~25):(60~70). S2.2 Add dopamine hydrochloride to the mixture, stir and disperse at 40~50℃ and 300~500rpm, then add alkaline additives to adjust the pH of the system to 8.0~8.5, and continue stirring for 15~30min to obtain a pre-modified solution. The amount of dopamine hydrochloride added is 0.5~1.5wt% of the polyester polymer mass, and the alkaline additives include at least one of ammonia, triethylamine, dimethylethanolamine or sodium hydroxide solution. S2.3 Add phenylboronic acid crosslinking agent to the pre-modified solution, add alkaline additive to adjust the pH of the system to 8.5~9.5, and heat to 60~70℃, stir at 400~600rpm for 1~2h to obtain the modified solution, wherein the amount of phenylboronic acid crosslinking agent added is 5~15wt% of the polyester polymer mass.

[0030] Compared to the original process of directly adding phenylboronic acid crosslinking agents to the mixture for crosslinking reaction, this embodiment introduces dopamine hydrochloride into the system beforehand and activates it under weakly alkaline conditions, enabling the introduction of a large number of catechol groups onto the surfaces of the polyester and propylene polymers. Since the catechol structure exhibits strong complexing and borate esterification reactivity with the phenylboronic acid groups (significantly higher than ordinary aliphatic hydroxyl groups), when the phenylboronic acid crosslinking agent is added in subsequent step S2.3, the phenylboronic acid groups preferentially form stable borate ester bonds with the catechol sites provided by dopamine. This serves as a bridge to further promote crosslinking between polyester and propylene polymer segments, increasing the enrichment and utilization efficiency of the phenylboronic acid crosslinking agent at the interface of the two polymers. Simultaneously, dopamine molecules can adsorb at the interface of the polyester and propylene phases, shortening the reaction distance between the phenylboronic acid groups and the active groups of the two polymers, increasing effective collision opportunities, thereby improving the crosslinking reaction rate and crosslinking uniformity.

[0031] S3. Add organosilicon polymer and metal salt to the modified solution, stir and disperse to obtain a high-temperature resistant water-based coating composition, wherein the organosilicon polymer contains hydroxyl groups and the metal ions in the metal salt are hard acid ions.

[0032] In step S3, the organosilicon polymer includes at least one of α,ω-dihydroxy polydimethylsiloxane, hydroxyl-terminated polydimethylsiloxane, and hydroxyl-terminated diphenyl silicone oil. The metal salt is a zirconium salt and / or an aluminum salt. The zirconium salt includes at least one of zirconium acetate, zirconium oxychloride, zirconium nitrate, and zirconium sulfate. The aluminum salt includes at least one of aluminum chloride, aluminum nitrate, aluminum sulfate, and aluminum acetate.

[0033] By introducing hydroxyl-containing organosilicon polymers and metal salts, the organosilicon polymers can participate in the construction of the cross-linked network through terminal hydroxyl groups, introducing high-bond-energy Si-O-Si segments into the resin system and improving the thermal stability of the network structure. Simultaneously, the siloxane segments gradually migrate and accumulate to the coating surface during film formation and curing, forming a low-surface-energy hydrophobic layer, reducing the coating's adsorption capacity for environmental moisture, and promoting the migration and escape of residual moisture from the system to the surface. On the other hand, the stearic acid metal ions in the metal salts can form stable coordination with oxygen-containing atoms in the polyester polymer, propylene polymer, organosilicon polymer, and borate ester network, further fixing and strengthening the covalent cross-linked network, improving the density and stability of the network structure, and reducing polar sites and moisture retention space.

[0034] Step S3 includes: S3.1 Add organosilicon polymer to the modified solution and disperse it for 15-30 min at 50-60℃ and stirring speed of 400-700 rpm. Then raise the temperature to 70-80℃, add dibutyltin dilaurate catalyst, and keep the reaction at 300-500 rpm for 30-60 min to obtain organosilicon polymer solution. The mass ratio of organosilicon polymer: dibutyltin dilaurate catalyst: deionized water is (1-5): (0.01-0.15): (60-70).

[0035] First, the organosilicon polymer is added to the modified solution and fully dispersed at 50-60℃. This facilitates the uniform distribution of the organosilicon polymer in the polyester / propylene composite system, ensuring sufficient contact between its hydroxyl functional groups and the hydroxyl, borate ester, and other polar groups in the system, creating a uniform reaction environment for subsequent network construction. Subsequently, the temperature is raised to 70-80℃ and a dibutyltin dilaurate catalyst is added. This effectively catalyzes the condensation reactions between silanol groups in the organosilicon polymer and between silanol groups and hydroxyl functional groups in the system, promoting the formation of an organosilicon cross-linked structure dominated by Si–O–Si bonds and enhancing the bonding between the organosilicon segments and the polyester / propylene polymer network. By controlling the catalyst dosage and reaction conditions, excessive local condensation of the organosilicon polymer, leading to aggregation and precipitation, can be avoided, improving system stability and reaction uniformity.

[0036] S3.2 Add the metal salt to the organosilicon polymer solution at 40~50℃ under stirring conditions, and stir at 40~50℃ and 400~700rpm for 20~40min to obtain a metal salt dispersion, wherein the amount of metal salt added is 1~5wt% of the mass of the polyester polymer.

[0037] Adding metal salts to the organosilicon polymerization solution and allowing them to disperse fully at 40-50℃ facilitates the uniform distribution of metal ions within the organosilicon-polyester-propylene composite system, preventing agglomeration or precipitation due to excessively high local concentrations and improving system stability. Since zirconium and aluminum ions are both hard acid ions, they can form stable coordination relationships with hard base sites such as carbonyl oxygen atoms in the polyester polymer, silicon-oxygen bonds in the organosilicon polymer, and oxygen atoms in the borate ester network. This further constructs a multi-point coordination crosslinking structure based on the existing covalent crosslinking network, increasing the crosslinking density and network integrity of the system. Simultaneously, because these polar sites are occupied by metal ions and form stable coordination bonds, their ability to form hydrogen bonds with water molecules is correspondingly reduced, thereby decreasing the adsorption and retention of moisture within the coating.

[0038] S3.3 Add deionized water to the metal salt dispersion to make the deionized water content in the system 60~70wt%, and add alkaline additives to adjust the pH of the system to 8.0~9.0. Then add polyether modified polysiloxane defoamer, stir at 30~45℃ and 300~500rpm for 10~20min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition. The alkaline additives include at least one of ammonia, triethylamine, dimethylethanolamine or sodium hydroxide solution, and the concentration of polyether modified polysiloxane defoamer in the high-temperature resistant water-based coating composition is 0.1~0.5wt%.

[0039] Adjusting the solid content of the system to a suitable range by adding deionized water helps optimize the application viscosity and storage stability of the high-temperature resistant waterborne coating composition. This ensures that the previously formed organosilicon crosslinking network, borate ester crosslinking network, and metal coordination network can be uniformly and stably dispersed in the aqueous phase system. Simultaneously, adjusting the pH of the system to 8.0-9.0 using alkaline additives helps maintain the stability of the borate ester bonds and metal coordination structure, preventing dissociation or aggregation of the crosslinking network due to pH fluctuations, thereby improving the stability of the system during long-term storage. Further addition of polyether-modified polysiloxane defoamers effectively eliminates microbubbles and residual bubbles introduced during preparation, reducing the risk of pinholes, craters, and void defects during film formation, and improving the density and surface smoothness of the coating. Filtering with a 200-mesh filter effectively removes trace impurity particles from the system, improving product stability and application adaptability, and avoiding surface defects caused by foreign particles. This results in a high-temperature resistant waterborne coating composition with more stable quality and superior film-forming effect.

[0040] Among them, the polyether-modified polysiloxane defoamers include at least one of BYK-024 defoamer, BYK-028 defoamer, BYK-022 defoamer, and BYK-025 defoamer. In one embodiment, the metal salt in step S3.2 is an activated metal salt solution, and the specific activation process is as follows: The metal salt is added to 2 to 4 times its own weight of deionized water, followed by the addition of an acid adjuster to adjust the pH of the system to 3.5 to 5.5. The temperature is controlled at 20 to 40°C, and the reaction is stirred at 300 to 600 rpm for 10 to 30 minutes to obtain a metal salt solution. The acid adjuster includes at least one of acetic acid, citric acid, or lactic acid.

[0041] Compared to directly adding metal salts to the system, this embodiment employs an acid regulator to pre-activate the metal salts, resulting in a more stable and highly reactive coordination state for the metal ions in the aqueous phase. This improves the uniformity and availability of the metal ions in the subsequent system. The activated metal ions can more fully coordinate with polar functional groups such as hydroxyl and carboxyl groups in polyester polymers, propylene polymers, and organosilicon polymers, promoting the construction of metal coordination crosslinking networks within the system and enhancing the interfacial bonding strength and structural synergy between different components.

[0042] In addition, a high-temperature resistant waterborne coating composition is proposed, which is prepared by the above-described method for preparing a high-temperature resistant waterborne coating composition.

[0043] For example, the present invention provides the following specific embodiments to illustrate the specific preparation method: Example 1: S1.1 Add polybutylene terephthalate to deionized water and stir at 450 rpm for 30 min. Then heat to 50°C and continue stirring for 20 min to obtain a premix. The mass ratio of polybutylene terephthalate to deionized water is 18:65. S1.2 Add trimethylolpropane to the premix, the amount of trimethylolpropane added is 10wt% of the mass of polybutylene terephthalate, control the stirring speed at 600rpm, stir and react at 70℃ for 60min to obtain a predispersant. S1.3 Add tetrabutyl titanate to the pre-dispersion liquid. The amount of tetrabutyl titanate added is 2wt% of the mass of polybutylene terephthalate. Control the stirring speed at 500 rpm and react at 70℃ for 50 min to obtain an activated polyester dispersion. S2.1 Add hydroxyethyl methacrylate to the activated polyester dispersion, control the temperature at 50℃, stir at 600 rpm, and continue stirring for 40 min to obtain a mixture, wherein the mass ratio of hydroxyethyl methacrylate to deionized water is 22:65; S2.2 Add 1,4-phenylenediboric acid to the mixture, adjust the pH of the system to 8.5-9.5 using triethylamine, and heat to 65℃. Stir at 500 rpm for 1.5 h to obtain a modified solution. The amount of 1,4-phenylenediboric acid added is 10 wt% of the mass of polybutylene terephthalate. S3.1 Add α,ω-dihydroxypolydimethylsiloxane to the modified solution and disperse it at 55℃ and 550rpm for 22min. Then raise the temperature to 75℃, add dibutyltin dilaurate catalyst, and keep the reaction at 400rpm for 45min to obtain organosilicon polymer solution. The mass ratio of α,ω-dihydroxypolydimethylsiloxane: dibutyltin dilaurate catalyst: deionized water is 3:0.08:65. S3.2. Zirconium sulfate was added to the organosilicon polymerization solution at 45°C under stirring. The mixture was stirred at 45°C and 550 rpm for 30 min to obtain a metal salt dispersion. The amount of zirconium sulfate added was 3 wt% of the mass of polybutylene terephthalate. S3.3 Add deionized water to the metal salt dispersion to make the deionized water content in the system 65wt%, and add triethylamine to adjust the pH of the system to 8.0~9.0. Then add BYK-024 defoamer, stir at 38℃ and 400rpm for 45min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition, wherein the concentration of BYK-024 defoamer in the high-temperature resistant water-based coating composition is 0.3wt%.

[0044] Example 2: S1.1 Add polybutylene terephthalate to deionized water and stir at 450 rpm for 30 min. Then heat to 50°C and continue stirring for 20 min to obtain a premix. The mass ratio of polybutylene terephthalate to deionized water is 18:65. S1.2 Add trimethylolpropane to the premix, the amount of trimethylolpropane added is 10wt% of the mass of polybutylene terephthalate, control the stirring speed at 600rpm, stir and react at 70℃ for 60min to obtain a predispersant. S1.3 Add tetrabutyl titanate to the pre-dispersion liquid. The amount of tetrabutyl titanate added is 2wt% of the mass of polybutylene terephthalate. Control the stirring speed at 500 rpm and react at 70℃ for 50 min to obtain an activated polyester dispersion. S2.1 Add hydroxyethyl methacrylate to the activated polyester dispersion, control the temperature at 50℃, stir at 600 rpm, and continue stirring for 40 min to obtain a mixture, wherein the mass ratio of hydroxyethyl methacrylate to deionized water is 22:65; S2.2 Add dopamine hydrochloride to the mixture and disperse it by stirring at 45℃ and 400 rpm. Then add triethylamine to adjust the pH of the system to 8.0~8.5 and continue stirring for 20 min to obtain the pre-modified solution. The amount of dopamine hydrochloride added is 1 wt% of the mass of polybutylene terephthalate. S2.3 Add 1,4-phenylenediboric acid to the pre-modified solution, adjust the pH of the system to 8.5-9.5 using triethylamine, and heat to 65℃. Stir at 500 rpm for 1.5 h to obtain the modified solution. The amount of 1,4-phenylenediboric acid added is 10 wt% of the mass of polybutylene terephthalate. S3.1 Add α,ω-dihydroxypolydimethylsiloxane to the modified solution and disperse it at 55℃ and 550rpm for 22min. Then raise the temperature to 75℃, add dibutyltin dilaurate catalyst, and keep the reaction at 400rpm for 45min to obtain organosilicon polymer solution. The mass ratio of α,ω-dihydroxypolydimethylsiloxane: dibutyltin dilaurate catalyst: deionized water is 3:0.08:65. S3.2. Zirconium sulfate was added to the organosilicon polymerization solution at 45°C under stirring. The mixture was stirred at 45°C and 550 rpm for 30 min to obtain a metal salt dispersion. The amount of zirconium sulfate added was 3 wt% of the mass of polybutylene terephthalate. S3.3 Add deionized water to the metal salt dispersion to make the deionized water content in the system 65wt%, and add triethylamine to adjust the pH of the system to 8.0~9.0. Then add BYK-024 defoamer, stir at 38℃ and 400rpm for 45min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition, wherein the concentration of BYK-024 defoamer in the high-temperature resistant water-based coating composition is 0.3wt%.

[0045] It is basically the same as Example 1, except that dopamine hydrochloride is added in step S2.

[0046] Example 3: S1.1 Add polybutylene terephthalate to deionized water and stir at 450 rpm for 30 min. Then heat to 50°C and continue stirring for 20 min to obtain a premix. The mass ratio of polybutylene terephthalate to deionized water is 18:65. S1.2 Add trimethylolpropane to the premix, the amount of trimethylolpropane added is 10wt% of the mass of polybutylene terephthalate, control the stirring speed at 600rpm, stir and react at 70℃ for 60min to obtain a predispersant. S1.3 Add tetrabutyl titanate to the pre-dispersion liquid. The amount of tetrabutyl titanate added is 2wt% of the mass of polybutylene terephthalate. Control the stirring speed at 500 rpm and react at 70℃ for 50 min to obtain an activated polyester dispersion. S2.1 Add hydroxyethyl methacrylate to the activated polyester dispersion, control the temperature at 50℃, stir at 600 rpm, and continue stirring for 40 min to obtain a mixture, wherein the mass ratio of hydroxyethyl methacrylate to deionized water is 22:65; S2.2 Add 1,4-phenylenediboric acid to the mixture, adjust the pH of the system to 8.5-9.5 using triethylamine, and heat to 65℃. Stir at 500 rpm for 1.5 h to obtain a modified solution. The amount of 1,4-phenylenediboric acid added is 10 wt% of the mass of polybutylene terephthalate. S3.1 Add α,ω-dihydroxypolydimethylsiloxane to the modified solution and disperse it at 55℃ and 550rpm for 22min. Then raise the temperature to 75℃, add dibutyltin dilaurate catalyst, and keep the reaction at 400rpm for 45min to obtain organosilicon polymer solution. The mass ratio of α,ω-dihydroxypolydimethylsiloxane: dibutyltin dilaurate catalyst: deionized water is 3:0.08:65. S3.2. Add zirconium sulfate to three times its own weight of deionized water, then add acetic acid to adjust the pH of the system to 3.5-5.5. Control the temperature at 30℃ and stir at 450 rpm for 20 min to obtain a zirconium sulfate solution. Add the zirconium sulfate solution to an organosilicon polymerization solution at 45℃ under stirring, and stir at 45℃ and 550 rpm for 30 min to obtain a metal salt dispersion. The amount of zirconium sulfate added is 3 wt% of the mass of polybutylene terephthalate. S3.3 Add deionized water to the metal salt dispersion to make the deionized water content in the system 65wt%, and add triethylamine to adjust the pH of the system to 8.0~9.0. Then add BYK-024 defoamer, stir at 38℃ and 400rpm for 45min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition, wherein the concentration of BYK-024 defoamer in the high-temperature resistant water-based coating composition is 0.3wt%.

[0047] It is basically the same as Example 1, except that the zirconium sulfate in step S3.2 is an activated zirconium sulfate solution.

[0048] Example 4: S1.1 Add polybutylene terephthalate to deionized water and stir at 450 rpm for 30 min. Then heat to 50°C and continue stirring for 20 min to obtain a premix. The mass ratio of polybutylene terephthalate to deionized water is 18:65. S1.2 Add trimethylolpropane to the premix, the amount of trimethylolpropane added is 10wt% of the mass of polybutylene terephthalate, control the stirring speed at 600rpm, stir and react at 70℃ for 60min to obtain a predispersant. S1.3 Add tetrabutyl titanate to the pre-dispersion liquid. The amount of tetrabutyl titanate added is 2wt% of the mass of polybutylene terephthalate. Control the stirring speed at 500 rpm and react at 70℃ for 50 min to obtain an activated polyester dispersion. S2.1 Add hydroxyethyl methacrylate to the activated polyester dispersion, control the temperature at 50℃, stir at 600 rpm, and continue stirring for 40 min to obtain a mixture, wherein the mass ratio of hydroxyethyl methacrylate to deionized water is 22:65; S2.2 Add 1,4-phenylenediboric acid to the mixture, adjust the pH of the system to 8.5-9.5 using triethylamine, and heat to 65℃. Stir at 500 rpm for 1.5 h to obtain a modified solution. The amount of 1,4-phenylenediboric acid added is 10 wt% of the mass of polybutylene terephthalate. S3.1 Add α,ω-dihydroxypolydimethylsiloxane to the modified solution and disperse it at 55℃ and 550rpm for 22min. Then raise the temperature to 75℃, add dibutyltin dilaurate catalyst, and keep the reaction at 400rpm for 45min to obtain organosilicon polymer solution. The mass ratio of α,ω-dihydroxypolydimethylsiloxane: dibutyltin dilaurate catalyst: deionized water is 3:0.08:65. S3.2. Aluminum sulfate was added to the organosilicon polymerization solution at 45°C under stirring. The mixture was stirred at 45°C and 550 rpm for 30 min to obtain a metal salt dispersion. The amount of aluminum sulfate added was 3 wt% of the mass of polybutylene terephthalate. S3.3 Add deionized water to the metal salt dispersion to make the deionized water content in the system 65wt%, and add triethylamine to adjust the pH of the system to 8.0~9.0. Then add BYK-024 defoamer, stir at 38℃ and 400rpm for 45min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition, wherein the concentration of BYK-024 defoamer in the high-temperature resistant water-based coating composition is 0.3wt%.

[0049] It is basically the same as Example 1, except that the metal salt used in step S3.2 is aluminum sulfate, that is, the metal salt in step S3 is an aluminum salt.

[0050] Comparative Example 1: S1.1 Add polybutylene terephthalate to deionized water and stir at 450 rpm for 30 min. Then heat to 50℃ and continue stirring for 20 min to obtain an activated polyester dispersion. The mass ratio of polybutylene terephthalate to deionized water is 18:65. S2.1 Add hydroxyethyl methacrylate to the activated polyester dispersion, control the temperature at 50℃, stir at 600 rpm, and continue stirring for 40 min to obtain a mixture, wherein the mass ratio of hydroxyethyl methacrylate to deionized water is 22:65; S2.2 Add 1,4-phenylenediboric acid to the mixture, adjust the pH of the system to 8.5-9.5 using triethylamine, and heat to 65℃. Stir at 500 rpm for 1.5 h to obtain a modified solution. The amount of 1,4-phenylenediboric acid added is 10 wt% of the mass of polybutylene terephthalate. S3.1 Add α,ω-dihydroxypolydimethylsiloxane to the modified solution and disperse it at 55℃ and 550rpm for 22min. Then raise the temperature to 75℃, add dibutyltin dilaurate catalyst, and keep the reaction at 400rpm for 45min to obtain organosilicon polymer solution. The mass ratio of α,ω-dihydroxypolydimethylsiloxane: dibutyltin dilaurate catalyst: deionized water is 3:0.08:65. S3.2. Zirconium sulfate was added to the organosilicon polymerization solution at 45°C under stirring. The mixture was stirred at 45°C and 550 rpm for 30 min to obtain a metal salt dispersion. The amount of zirconium sulfate added was 3 wt% of the mass of polybutylene terephthalate. S3.3 Add deionized water to the metal salt dispersion to make the deionized water content in the system 65wt%, and add triethylamine to adjust the pH of the system to 8.0~9.0. Then add BYK-024 defoamer, stir at 38℃ and 400rpm for 45min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition, wherein the concentration of BYK-024 defoamer in the high-temperature resistant water-based coating composition is 0.3wt%.

[0051] It is basically the same as Example 1, except that polyol auxiliaries and transesterification auxiliaries are not used in step S1.

[0052] Comparative Example 2: S1.1 Add polybutylene terephthalate to deionized water and stir at 450 rpm for 30 min. Then heat to 50°C and continue stirring for 20 min to obtain a premix. The mass ratio of polybutylene terephthalate to deionized water is 18:65. S1.2 Add trimethylolpropane to the premix, the amount of trimethylolpropane added is 10wt% of the mass of polybutylene terephthalate, control the stirring speed at 600rpm, stir and react at 70℃ for 60min to obtain a predispersant. S1.3 Add tetrabutyl titanate to the pre-dispersion liquid. The amount of tetrabutyl titanate added is 2wt% of the mass of polybutylene terephthalate. Control the stirring speed at 500 rpm and react at 70℃ for 50 min to obtain an activated polyester dispersion. S2. Add hydroxyethyl methacrylate to the activated polyester dispersion, control the temperature at 50℃, stir at 600 rpm, and continue stirring for 40 min to obtain a mixture, wherein the mass ratio of hydroxyethyl methacrylate to deionized water is 22:65. S3.1 Add α,ω-dihydroxypolydimethylsiloxane to the mixture and disperse it at 55℃ and 550rpm for 22min. Then raise the temperature to 75℃, add dibutyltin dilaurate catalyst, and keep the reaction at 400rpm for 45min to obtain organosilicon polymer solution. The mass ratio of α,ω-dihydroxypolydimethylsiloxane: dibutyltin dilaurate catalyst: deionized water is 3:0.08:65. S3.2. Zirconium sulfate was added to the organosilicon polymerization solution at 45°C under stirring. The mixture was stirred at 45°C and 550 rpm for 30 min to obtain a metal salt dispersion. The amount of zirconium sulfate added was 3 wt% of the mass of polybutylene terephthalate. S3.3 Add deionized water to the metal salt dispersion to make the deionized water content in the system 65wt%, and add triethylamine to adjust the pH of the system to 8.0~9.0. Then add BYK-024 defoamer, stir at 38℃ and 400rpm for 45min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition, wherein the concentration of BYK-024 defoamer in the high-temperature resistant water-based coating composition is 0.3wt%.

[0053] It is basically the same as Example 1, except that 1,4-phenylenediboric acid is not used in step S2, that is, phenylboronic acid crosslinking agent is not used in step S2.

[0054] Comparative Example 3: S1.1 Add polybutylene terephthalate to deionized water and stir at 450 rpm for 30 min. Then heat to 50°C and continue stirring for 20 min to obtain a premix. The mass ratio of polybutylene terephthalate to deionized water is 18:65. S1.2 Add trimethylolpropane to the premix, the amount of trimethylolpropane added is 10wt% of the mass of polybutylene terephthalate, control the stirring speed at 600rpm, stir and react at 70℃ for 60min to obtain a predispersant. S1.3 Add tetrabutyl titanate to the pre-dispersion liquid. The amount of tetrabutyl titanate added is 2wt% of the mass of polybutylene terephthalate. Control the stirring speed at 500 rpm and react at 70℃ for 50 min to obtain an activated polyester dispersion. S2.1 Add hydroxyethyl methacrylate to the activated polyester dispersion, control the temperature at 50℃, stir at 600 rpm, and continue stirring for 40 min to obtain a mixture, wherein the mass ratio of hydroxyethyl methacrylate to deionized water is 22:65; S2.2 Add 1,4-phenylenediboric acid to the mixture, adjust the pH of the system to 8.5-9.5 using triethylamine, and heat to 65℃. Stir at 500 rpm for 1.5 h to obtain a modified solution. The amount of 1,4-phenylenediboric acid added is 10 wt% of the mass of polybutylene terephthalate. S3.1. Zirconium sulfate was added to the modified solution at 45°C under stirring. The mixture was stirred at 45°C and 550 rpm for 30 min to obtain a metal salt dispersion. The amount of zirconium sulfate added was 3 wt% of the mass of polybutylene terephthalate. S3.2 Add deionized water to the metal salt dispersion to make the deionized water content in the system 65wt%, and add triethylamine to adjust the pH of the system to 8.0~9.0. Then add BYK-024 defoamer, stir at 38℃ and 400rpm for 45min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition, wherein the concentration of BYK-024 defoamer in the high-temperature resistant water-based coating composition is 0.3wt%.

[0055] It is basically the same as Example 1, except that α,ω-dihydroxypolydimethylsiloxane was not added in step S3, that is, no organosilicon polymer was used in step S3.

[0056] Comparative Example 4: S1.1 Add polybutylene terephthalate to deionized water and stir at 450 rpm for 30 min. Then heat to 50°C and continue stirring for 20 min to obtain a premix. The mass ratio of polybutylene terephthalate to deionized water is 18:65. S1.2 Add trimethylolpropane to the premix, the amount of trimethylolpropane added is 10wt% of the mass of polybutylene terephthalate, control the stirring speed at 600rpm, stir and react at 70℃ for 60min to obtain a predispersant. S1.3 Add tetrabutyl titanate to the pre-dispersion liquid. The amount of tetrabutyl titanate added is 2wt% of the mass of polybutylene terephthalate. Control the stirring speed at 500 rpm and react at 70℃ for 50 min to obtain an activated polyester dispersion. S2.1 Add hydroxyethyl methacrylate to the activated polyester dispersion, control the temperature at 50℃, stir at 600 rpm, and continue stirring for 40 min to obtain a mixture, wherein the mass ratio of hydroxyethyl methacrylate to deionized water is 22:65; S2.2 Add 1,4-phenylenediboric acid to the mixture, adjust the pH of the system to 8.5-9.5 using triethylamine, and heat to 65℃. Stir at 500 rpm for 1.5 h to obtain a modified solution. The amount of 1,4-phenylenediboric acid added is 10 wt% of the mass of polybutylene terephthalate. S3.1 Add α,ω-dihydroxypolydimethylsiloxane to the modified solution and disperse it at 55℃ and 550rpm for 22min. Then raise the temperature to 75℃, add dibutyltin dilaurate catalyst, and keep the reaction at 400rpm for 45min to obtain organosilicon polymer solution. The mass ratio of α,ω-dihydroxypolydimethylsiloxane: dibutyltin dilaurate catalyst: deionized water is 3:0.08:65. S3.2 Add deionized water to the organosilicon polymerization solution to make the deionized water content in the system 65wt%, and add triethylamine to adjust the pH of the system to 8.0~9.0. Then add BYK-024 defoamer, stir at 38℃ and 400rpm for 45min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition, wherein the concentration of BYK-024 defoamer in the high-temperature resistant water-based coating composition is 0.3wt%.

[0057] It is basically the same as Example 1, except that zirconium sulfate is not used in step S3, that is, no metal salt is used in step S3.

[0058] Comparative Example 5: S1.1 Add polybutylene terephthalate to deionized water and stir at 450 rpm for 30 min. Then heat to 50°C and continue stirring for 20 min to obtain a premix. The mass ratio of polybutylene terephthalate to deionized water is 18:65. S1.2 Add trimethylolpropane to the premix, the amount of trimethylolpropane added is 10wt% of the mass of polybutylene terephthalate, control the stirring speed at 600rpm, stir and react at 70℃ for 60min to obtain a predispersant. S1.3 Add tetrabutyl titanate to the pre-dispersion liquid. The amount of tetrabutyl titanate added is 2wt% of the mass of polybutylene terephthalate. Control the stirring speed at 500 rpm and react at 70℃ for 50 min to obtain an activated polyester dispersion. S2.1 Add hydroxyethyl methacrylate to the activated polyester dispersion, control the temperature at 50℃, stir at 600 rpm, and continue stirring for 40 min to obtain a mixture, wherein the mass ratio of hydroxyethyl methacrylate to deionized water is 22:65; S2.2 Add 1,4-phenylenediboric acid to the mixture, adjust the pH of the system to 8.5-9.5 using triethylamine, and heat to 65℃. Stir at 500 rpm for 1.5 h to obtain a modified solution. The amount of 1,4-phenylenediboric acid added is 10 wt% of the mass of polybutylene terephthalate. S3.1 Add α,ω-dihydroxypolydimethylsiloxane to the modified solution and disperse it at 55℃ and 550rpm for 22min. Then raise the temperature to 75℃, add dibutyltin dilaurate catalyst, and keep the reaction at 400rpm for 45min to obtain organosilicon polymer solution. The mass ratio of α,ω-dihydroxypolydimethylsiloxane: dibutyltin dilaurate catalyst: deionized water is 3:0.08:65. S3.2. Zinc sulfate was added to the organosilicon polymerization solution at 45°C under stirring. The mixture was stirred at 45°C and 550 rpm for 30 min to obtain a metal salt dispersion. The amount of zinc sulfate added was 3 wt% of the mass of polybutylene terephthalate. S3.3 Add deionized water to the metal salt dispersion to make the deionized water content in the system 65wt%, and add triethylamine to adjust the pH of the system to 8.0~9.0. Then add BYK-024 defoamer, stir at 38℃ and 400rpm for 45min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition, wherein the concentration of BYK-024 defoamer in the high-temperature resistant water-based coating composition is 0.3wt%.

[0059] It is basically the same as Example 1, except that in step S3.2, zinc sulfate of equal mass is used instead of zirconium sulfate.

[0060] Comparative Example 6: S1. Add polybutylene terephthalate to deionized water and stir at 450 rpm for 30 min. Then heat to 50°C and continue stirring for 20 min to obtain an activated polyester dispersion. The mass ratio of polybutylene terephthalate to deionized water is 18:65. S2. Add hydroxyethyl methacrylate to the activated polyester dispersion, control the temperature at 50℃, stir at 600 rpm, and continue stirring for 40 min to obtain a mixture, wherein the mass ratio of hydroxyethyl methacrylate to deionized water is 22:65. S3. Add deionized water to the mixture to make the deionized water content in the system 65wt%, and add triethylamine to adjust the pH of the system to 8.0~9.0. Then add BYK-024 defoamer, stir at 38℃ and 400rpm for 45min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition, wherein the concentration of BYK-024 defoamer in the high-temperature resistant water-based coating composition is 0.3wt%.

[0061] Performance testing: VOC content: Tested in accordance with GB / T23985-2009.

[0062] Moisture removal time: The high-temperature resistant water-based coating composition was applied to a clean aluminum plate by scraping, with the coating thickness controlled at 150 μm. After standing and leveling for 20 min at 25℃ and 50%RH, the sample was then placed in a sealed constant-temperature drying chamber with weighing function and subjected to continuous dynamic drying test at 120℃. The sampling interval was set to 10 s, and the change in mass over time was recorded by the data acquisition system. When the rate of mass change per unit time (1 min) was less than 0.01% / min for 3 consecutive mins, the system was determined to have reached a quasi-constant weight state, and the time corresponding to this state was taken as the moisture removal time.

[0063] Performance tests before and after aging: The high-temperature resistant water-based coating composition was applied to a clean aluminum plate by scraping and then peeled off to form a film. The coating thickness was controlled at 150 μm. Dumbbell-shaped specimens were prepared according to GB / T 1040, and their initial tensile strength and elongation at break were tested. Subsequently, the specimens were placed in a constant temperature oven at 250℃ for heat aging treatment for 24 h. After heat aging, the specimens were removed and allowed to stand at room temperature for 30 min to recover. Their tensile strength and elongation at break were tested again, and the retention rate was calculated according to the performance retention rate formula (retention rate = performance after aging / initial performance × 100%).

[0064] The test results are shown in Table 1.

[0065] Table 1 Performance Tests of Coating Compositions: As shown in Table 1, the VOC content of each example and comparative example was at a low level with no significant difference, indicating that the addition of each component did not have a negative impact on the VOC index. In terms of water removal time, Examples 1-4 were significantly better than the comparative examples. Among them, Comparative Example 3, due to the lack of organosilicon polymer, had a significantly different dehydration time compared to the examples, reaching 90 min. Comparative Example 6, due to the simultaneous absence of polyol auxiliaries, phenylboronic acid crosslinking agents, organosilicon polymers, and metal salts, had the longest dehydration time, reaching 120 min. In terms of high temperature resistance, Examples 1-4 were also significantly better than all comparative examples in terms of retention rate of tensile strength and elongation at break after aging. Among them, Comparative Example 2, which lacked phenylboronic acid crosslinking agents, and Comparative Example 3, which lacked organosilicon, had significantly lower retention rates. Finally, as shown in Examples 1 and Comparative Example 5, by using zinc salt instead of zirconium salt in the metal salt, compared to Comparative Example 4 without the use of metal salt, although zinc salt also improved the performance, it was significantly lower than that of zirconium salt.

[0066] Other embodiments of this disclosure will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This application is intended to cover any variations, uses, or adaptations of this disclosure that follow the general principles of this disclosure and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of this disclosure are indicated by the following claims.

Claims

1. A method for preparing a high-temperature resistant water-based coating composition, characterized in that, The preparation method includes the following steps: S1. Add polyester polymer to deionized water and stir until homogeneous to obtain a premix. Then add polyol auxiliaries and transesterification auxiliaries, heat and stir to react, and obtain activated polyester dispersion. S2. Add propylene polymer and phenylboronic acid crosslinking agent to the activated polyester dispersion, adjust the pH to alkaline, heat and stir to react, and obtain a modified solution, wherein the propylene polymer contains hydroxyl groups; S3. Add organosilicon polymer and metal salt to the modified solution, stir and disperse to obtain a high-temperature resistant water-based coating composition, wherein the organosilicon polymer contains hydroxyl groups and the metal ions in the metal salt are hard acid ions.

2. The method for preparing a high-temperature resistant water-based coating composition according to claim 1, characterized in that, Step S1 includes: S1.1 Add the polyester polymer to deionized water and stir at 300-600 rpm for 20-40 min. Then raise the temperature to 40-60℃ and continue stirring for 10-30 min to obtain a premix. The mass ratio of polyester polymer to deionized water is (15-20):(60-70). S1.2 Add polyol additive to the premix, the amount of polyol additive added is 3~20wt% of the polyester polymer mass, control the stirring speed at 400~800rpm, stir and react at 60~80℃ for 30~90min to obtain predispersion; S1.3 Add transesterification aid to the pre-dispersion liquid. The amount of transesterification aid added is 0.1~5wt% of the polyester polymer mass. Control the stirring speed at 300~700rpm and react at 60~80℃ for 40~60min to obtain activated polyester dispersion.

3. The method for preparing a high-temperature resistant water-based coating composition according to claim 2, characterized in that, In step S1, the polyester polymer includes at least one of polyethylene terephthalate, polybutylene terephthalate, polypropylene terephthalate, polybutylene adipate, and polyethylene adipate; the polyol auxiliaries include at least one of ethylene glycol, propylene glycol, diethylene glycol, neopentyl glycol, trimethylolpropane, pentaerythritol, and polyethylene glycol; and the transesterification auxiliaries include at least one of tetrabutyl titanate, tetraisopropyl titanate, titanium acetylacetonate, stannous octoate, and dibutyltin dilaurate.

4. The method for preparing a high-temperature resistant water-based coating composition according to claim 1, characterized in that, Step S2 includes: S2.1 Add the propylene polymer to the activated polyester dispersion, control the temperature at 40~60℃, stir at 400~800rpm, and continue stirring for 20~60min to obtain a mixture, wherein the mass ratio of propylene polymer to deionized water is (20~25):(60~70); S2.2 Add a phenylboronic acid crosslinking agent to the mixture, adjust the pH of the system to 8.5-9.5 using an alkaline additive, heat to 60-70℃, and stir at 400-600 rpm for 1-2 hours to obtain a modified solution. The amount of phenylboronic acid crosslinking agent added is 5-15 wt% of the polyester polymer mass, and the alkaline additive includes at least one of ammonia, triethylamine, dimethylethanolamine, or sodium hydroxide solution.

5. The method for preparing a high-temperature resistant water-based coating composition according to claim 1, characterized in that, Step S2 includes: S2.1 Add the propylene polymer to the activated polyester dispersion, control the temperature at 40~60℃, stir at 400~800rpm, and continue stirring for 20~60min to obtain a mixture, wherein the mass ratio of propylene polymer to deionized water is (20~25):(60~70); S2.2 Add dopamine hydrochloride to the mixture, stir and disperse at 40~50℃ and 300~500rpm, then add alkaline additives to adjust the pH of the system to 8.0~8.5, and continue stirring for 15~30min to obtain a pre-modified solution. The amount of dopamine hydrochloride added is 0.5~1.5wt% of the polyester polymer mass, and the alkaline additives include at least one of ammonia, triethylamine, dimethylethanolamine or sodium hydroxide solution. S2.3 Add phenylboronic acid crosslinking agent to the pre-modified solution, add alkaline additive to adjust the pH of the system to 8.5~9.5, and heat to 60~70℃, stir at 400~600rpm for 1~2h to obtain the modified solution, wherein the amount of phenylboronic acid crosslinking agent added is 5~15wt% of the polyester polymer mass.

6. A method for preparing a high-temperature resistant water-based coating composition according to claim 4 or 5, characterized in that, In step S2, the propylene polymer includes at least one of hydroxyethyl methacrylate, hydroxyethyl acrylate, and hydroxypropyl methacrylate, and the phenylboronic acid crosslinking agent includes at least one of phenylboronic acid, 1,4-phenyldiboronic acid, and 4,4'-biphenyldiboronic acid.

7. The method for preparing a high-temperature resistant water-based coating composition according to claim 1, characterized in that, Step S3 includes: S3.1 Add organosilicon polymer to the modified solution and disperse it for 15-30 min at 50-60℃ and stirring speed of 400-700 rpm. Then raise the temperature to 70-80℃, add dibutyltin dilaurate catalyst, and keep the reaction at 300-500 rpm for 30-60 min to obtain organosilicon polymer solution. The mass ratio of organosilicon polymer: dibutyltin dilaurate catalyst: deionized water is (1-5): (0.01-0.15): (60-70). S3.

2. The metal salt is added to the organosilicon polymer solution at 40-50°C under stirring. The mixture is stirred at 40-50°C and 400-700 rpm for 20-40 minutes to obtain a metal salt dispersion. The amount of metal salt added is 1-5 wt% of the mass of the polyester polymer. S3.3 Add deionized water to the metal salt dispersion to make the deionized water content in the system 60~70wt%, and add alkaline additives to adjust the pH of the system to 8.0~9.

0. Then add polyether-modified polysiloxane defoamer, stir at 30~45℃ and 300~500rpm for 10~20min, filter through a 200-mesh filter to obtain a high-temperature resistant water-based coating composition. The alkaline additives include at least one of ammonia, triethylamine, dimethylethanolamine or sodium hydroxide solution, and the concentration of polyether-modified polysiloxane defoamer in the high-temperature resistant water-based coating composition is 0.1~0.5wt%.

8. The method for preparing a high-temperature resistant water-based coating composition according to claim 7, characterized in that, In step S3, the organosilicon polymer includes at least one of α,ω-dihydroxy polydimethylsiloxane, hydroxyl-terminated polydimethylsiloxane, and hydroxyl-terminated diphenyl silicone oil. The metal salt is a zirconium salt and / or an aluminum salt. The zirconium salt includes at least one of zirconium acetate, zirconium oxychloride, zirconium nitrate, and zirconium sulfate. The aluminum salt includes at least one of aluminum chloride, aluminum nitrate, aluminum sulfate, and aluminum acetate.

9. The method for preparing a high-temperature resistant water-based coating composition according to claim 7, characterized in that, In step S3.2, the metal salt is an activated metal salt solution. The specific activation process is as follows: The metal salt is added to 2 to 4 times its own weight of deionized water, followed by the addition of an acid adjuster to adjust the pH of the system to 3.5 to 5.

5. The temperature is controlled at 20 to 40°C, and the reaction is stirred at 300 to 600 rpm for 10 to 30 minutes to obtain a metal salt solution. The acid adjuster includes at least one of acetic acid, citric acid, or lactic acid.

10. A high-temperature resistant water-based coating composition, characterized in that, The high-temperature resistant water-based coating composition is prepared by the preparation method of any one of the high-temperature resistant water-based coating compositions according to claims 1-9.